Number of Ideal Stages as an Efficiency Parameter for Displacement Washing - Potůček, František (Editura Academiei Romane, 2019)
In this paper, the concept of the number of ideal stages of dilution and thickening commonly used for the description of counter-current washing systems was applied to quantify the efficiency of displacement washing of pulp. Two kraft pulps cooked from beech and spruce with one soda pulp from rapeseed straw and delignified to the relative high kappa number ranging of 49.7 to 51.6 were undergone to the displacement washing using water as the wash liquid. Besides the traditional displacement ratio, the efficiency of displacement washing was expressed by the number of ideal counter-current washing stages as a function of the Péclet number and dimensionless dispersion length. The results described by the correlation equations showed that the kraft pulps cooked form beech and spruce seem to be better washable comparing to soda rapeseed pulp.
Počet ideálních stupňů jako parametr účinnosti vytěsňovacího praní
Keywords: pulp; displacement washing; washing efficiency; ideal stage; displacement ratio; buničina; vytěsňovací praní; účinnost praní; ideální stupeň; vytěsňovací poměr